ANALISIS PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN DI BEI - Hidayah Lubis, syarif; Hardi Bahar; Agung Joni Saputra (Fortunate Business Review, 2021)
Companies that have good financial analysis performance on time in submitting financial statements, poor financial performance can be used with several ratios namely profitability, solvency and company size (size). The purpose of this study was to determine the effect of profitability, solvency and firm size on the timeliness of submitting financial statements of companies listed on BE. The method used is descriptive quantitative with secondary documentation technique data collection. The population in this study is the target population (target population) which found 60 companies engaged in the consumer goods industry sector and the type of sample in this study was Non Probability Sampling which opened 34 companies. The partial results of profitability have no significant effect on the timeliness of submitting financial statements so that hypothesis H1 is rejected, solvency has no significant effect on the timeliness of submitting financial statements so that hypothesis H2 is rejected, company size has a significant effect on the timeliness of submitting reports so that hypothesis H3 is accepted, simultaneously profitability , solvency and firm size affect the timeliness of financial report submission, thus H4 is accepted